Institutional trust, scientific literacy, and information sources: What factors determine people's attitudes toward COVID-19 vaccines of different origins in China? - Ye, Yanyu; Su, Zhenhua; Shi, Chunyu (Frontiers in Public Health, 2023)
Objective: This study aimed to investigate the different attitudes of Chinese residents toward COVID-19 vaccines produced in China and the United States in an emergency context, and then explored possible explanations for these different attitudes. Methods: Using data collected online in May 2021, we compared Chinese citizens’ attitudes toward vaccines originating from China and the US and then adopted ordered logistic models to examine how trust in institutions, scientific literacy, and information sources influence their attitudes toward different vaccines. Results: A total of 2038 respondents completed the survey. Participants reported very different levels of trust in Chinese and American vaccines. The main finding of this paper is that individuals who trust in Chinese institutions, especially those who trust in domestic scientists, typically feel encouraged to also place their trust in domestic vaccines and to distrust those from the US. These individuals’ higher evaluation of Chinese government performance makes them more willing to vaccinate with domestic vaccines and less likely to seek US vaccines. Levels of scientific literacy, furthermore, seem to have little influence on attitudes toward different vaccines. Meanwhile, respondents who acquire health information from biomedical journals are more likely to hold a positive view of US vaccines, and these individuals contribute to bridging the gap between levels of trust in Chinese and US vaccines. Conclusions: In contrast with previous findings about Chinese attitudes toward imported vaccines, our respondents are more convinced of the safety and effectiveness of domestic vaccines than of US ones. This trust gap does not arise out of actual disparity in the quality and safety of the different vaccines per se. Instead, it is a cognition concern that is closely bound up with individuals’ trust in domestic institutions. People’s attitudes toward vaccines of different origins in an emergency context are more influenced by socio-political beliefs than by concern with objective information and knowledge.